Variable Surface Charge of Humic Acid-Ferrihydrite Composite: Influence of Electrolytes on Ciprofloxacin Adsorption - Escudey-Castro, A; Escudey-Castro, A; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Gacitua-Santalices, M; Gacitua-Santalices, M (Elsevier B.V., 2020)
Antimicrobial compounds are found in a range of environments as pollutants. Here, we evaluated the influence of two common anions, NO3− and PO43-, on ciprofloxacin adsorption on humic acid/ferrihydrite composite (HA-DIG/Fh), synthetic ferrihydrite (Fh), and humic acid (HA-DIG) under controlled pH (7.0), ionic strength (0.1 M) and temperature (25 °C). All materials were characterized by isoelectric point (IEP), while the composite and the iron oxide were characterized by Mössbauer spectroscopy. Kinetic and isotherm adsorption studies were carried out using cyclic voltammetry (in KH2PO4) and square wave voltammetry (in KNO3). The application of kinetic models for both anions revealed Fh to fit to a pseudo second order model (R2 = 0.941); while HA-DIG (R2 = 0.950) and HA-DIG/Fh (R2 = 0.993) were fitted to pseudo first order models. The adsorption results showed a high dependency electrolyte, especially in Fh, where different shape curves (H-type in KNO3 and C-type in KH2PO4) and maximum experimental adsorbed amount Cm were observed. This finding is supported by the distinct IEP values and change in sign of surface charge between the two ions. Finally, results suggest that HA-DIG could be potentially used in environmental remediation to remove antibiotics from natural matrices, though the risk of antibiotic transportation increased with depth in the soil profile. © 2019 Elsevier B.V.
Keywords: Antibiotics; Natural organic matter; Iron oxides; Mossbauer spectroscopy; Sorption models